Risk factors for urosepsis following ureteroscopic lithotripsy: a systematic review and meta-analysis - Dai, Lifei; Xiang, Junlian; Liu, Xiaoli; Wen, Xiaoyan; Tan, Lin; Zhang, Jiali (Frontiers in Surgery, 2025)
BackgroundUreteroscopic lithotripsy (URSL) is the preferred treatment for urinary tract stones, with urosepsis being its most severe postoperative complication. Although previous studies have investigated risk factors for urosepsis after URSL, significant variations exist in reported risk factors and their associated odds ratios (OR), leading to inconsistent findings across studies. This systematic review and meta-analysis investigated the risk factors for urosepsis after URSL, aiming to establish a scientific foundation for early clinical identification and to reduce the incidence and mortality of this complication.MethodsCase-control and cohort studies on factors influencing urosepsis after URSL were systematically retrieved from major public medical databases, including PubMed, Web of Science, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Data, and Chinese Science and Technology Journal Database, up to January 31, 2025. Two researchers independently conducted literature screening, data extraction, quality assessment, and meta-analysis using Stata versions 15.1 and 18.0.ResultsA total of 26 studies were included in this analysis, comprising 12,394 patients, of whom 861 patients developed urosepsis. The influencing factors for urosepsis included stone size[OR = 3.10, 95% CI (1.20,8.00), P = 0.002], number of stones [OR = 7.59, 95% confidence interval (CI): 3.82, 15.08; P < 0.001], history of urinary tract infection (OR = 5.96, 95% CI: 4.12, 8.60; P < 0.001), positive urine culture (OR = 4.95, 95% CI: 3.90, 6.28; P < 0.001), positive urinary nitrite (OR = 7.68, 95% CI: 1.03, 52.27; P = 0.047], C-reactive protein (OR = 4.3, 95% CI: 1.06, 17.49; P = 0.042), diabetes (OR = 3.60, 95% CI: 3.11, 4.16; P < 0.001), operation time (OR = 1.09, 95% CI: 1.07, 1.11; P < 0.001), and stent placement (OR = 3.71, 95% CI: 1.94, 7.09; P < 0.001].ConclusionUrosepsis following URSL is associated with a high mortality rate and significantly threatens patient safety and quality of life. Early identification of the factors influencing urosepsis is crucial to reduce its incidence and improve patient outcomes.Systematic Review RegistrationPROSPERO CRD42025641787.